Direct Torque Control of BLDC Motor with Constant Switching Frequency - Adeline Lukar Herlino; Auzani Jidin; Tole Sutikno; Mustafa Manap; Muhd Khairi Abdul Rahim; Ahmad Faiz Noor Azam (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Direct torque control (DTC) has become a popular technique for brushless motor control because it provides fast dynamic torque response. Hysteresis band control is the most popular techniques used in the DTC BLDC motor drive caused the simplest technique. However the conventional DTC have problems as switching frequency that varies with operating conditions and high torque ripple. This paper presents direct torque control (DTC) of BLDC motor with constant switching frequency torque controller. The torque ripple will get reduced by this method constant switching frequency operation. The feasibility of this method in minimizing the torque ripple is verified through some simulation results.